Affecting care: Maggie's Centres and the orchestration of architectural atmospheres. (November 2019) - Martin, Daryl; Nettleton, Sarah; Buse, Christina
Abstract: This article presents research on the architecture of Maggie's Centres, a series of buildings for those with cancer, their families and friends. In particular, we explore the way in which their architectural atmospheres are spoken of by architects who have designed individual Maggie's Centres, in interviews with staff members and volunteers in the buildings and in focus groups with visitors to their sites. We bring together qualitative research from two separate projects, and present findings from interviews, across the UK and internationally, with 66 visitors, 22 staff members and 7 architects of Maggie's Centres. How our research participants discussed the atmospheres of their Maggie's Centres is broken down into an analysis of, respectively, how building materials are used in these buildings; how colour and light are experienced in the buildings, and how the shape of the buildings in themselves affect the ways in which people use the spaces. These separate aspects of the buildings combine to become what can be described as the generators of architectural atmospheres. We discuss how architects, staff members, volunteers and visitors translated their intuition of intangible atmospheres into a recognition of architectural qualities, and linked these to questions of care. Maggie's Centres, we argue, are emotionally charged buildings that shape the ways in which care is staged, practiced and experienced in everyday ways, through the orchestration of architectural atmospheres. We use the example of Maggie's Centres as a comparison with how social scientists have characterised the design of mainstream hospital settings, in order to draw out the implications for questions of healing and recovery from illness, and how buildings may hold the potential to affect care. Highlights: Building design is a vital aspect of the experience of health and illness. Maggie's Centres demonstrate the scope of buildings to affect care. Architects, visitors and staff highlight agency of buildings for cancer care. Materials, colour, light and architectural form key to how buildings enable care. Healthcare architecture benefits from attention to its atmospheric qualities.